PARASOCIAL COMMUNICATION ON SOCIAL NETWORKS: CASE STUDY OF NOVAK ĐOKOVIĆ AND HIS FOLLOWERS (Heritage, 2023)
The paper deals with the presentation and analysis of parasocial communications using relevant communication theories and the psychology of media, communications and relationships, because new patterns of choice in communication processes have changed the way an individual enters into social relationships - from given (imposed) to chosen. The approach is expanded with a practical aspect - research into the parasocial communication of Novak Djokovic and his followers on the official Facebook page of our tennis player. The period during Roland Garros 2022 was taken for two reasons: it is one of the most important tournaments and the first big one after the break caused by refusing to be vaccinated against Covid/19 virus, which is why Djokovic did not participate in two of the four biggest tournaments before that year, and that at the same time he defended the position of the first player on the ATP list, which is why the engagement of followers was more intense than average. The approach is extended with a practical aspect - research into the parasocial communication of Novak Djokovic and his followers on his official Facebook page. The ways in which Djokovic addresses his fans and the content of his posts on Facebook encourage the development of a sense of closeness and familiarity among the audience. The research proved that parasocial interaction is realized in virtual communication in which Novak Djokovic's followers use the opportunity to address him through Facebook and often expect a return reaction. Social networks thus realize their procreative function, which is manifested in parasocial interaction through the exchange of messages, participation, togetherness and feedback simulation. Parasocial relationships are characterized by non-reciprocity, i.e. the fact that only one party knows a lot about the other, while the reverse is not true.
Keywords: parasocial communication, followers, social networks, Novak Djokovic, Facebook